A Shear Stress Regulated Assembly Route to Silica Nanotubes and Their Closely Packed Hollow Mesostructures1. Issue 44 (5th September 2013) - Wang, Chun; Wei, Jing; Yue, Qin; Luo, Wei; Li, Yuhui; Wang, Minghong; Deng, Yonghui; Zhao, Dongyuan
<x xml:space="preserve">Abstract</x> Ready to load: A shear stress regulated assembly route has been used to fabricate silica nanotubes and hollow mesostructures thereof. The packed silica nanotubes were employed as support for loading gold nanoparticles for efficiently catalyzing the epoxidation of styrene with high conversion and selectivity towards styrene oxide.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>